2011
DOI: 10.1093/jac/dkr410
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of Helicobacter pylori to six antibiotics currently used in Spain

Abstract: Our study confirms an increasing rate of resistance to levofloxacin that equals that of clarithromycin in our healthcare area. This fact may reflect a wide and indiscriminate use of the former antibiotic and could account for a loss of clinical effectiveness of levofloxacin-containing regimens. Moreover, clarithromycin resistance rates remain stable, which could allow us to maintain its use in our area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
40
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 21 publications
11
40
3
Order By: Relevance
“…Wueppenhorstet al (20) and Larsen et al (21) in Norway reported H. pylori amoxicillin and tetracycline resistance rates of 1.4% and 0% in Germany and 10% and 0% in Norway, respectively. Cuadrado-Lavínet al (27) in Spain and Georgopoulos et al (17) in Greece reported no amoxicillin resistance. Boyanova et al (18) reported 2% tetracycline resistance.…”
Section: Ethical Considerationsmentioning
confidence: 93%
See 2 more Smart Citations
“…Wueppenhorstet al (20) and Larsen et al (21) in Norway reported H. pylori amoxicillin and tetracycline resistance rates of 1.4% and 0% in Germany and 10% and 0% in Norway, respectively. Cuadrado-Lavínet al (27) in Spain and Georgopoulos et al (17) in Greece reported no amoxicillin resistance. Boyanova et al (18) reported 2% tetracycline resistance.…”
Section: Ethical Considerationsmentioning
confidence: 93%
“…The metronidazole resistance of H. pylori is closely related to geographic location and to the use of this drug for its antiparasitic activity. In African countries, the prevalence of metronidazole resistance is approximately 90%; however, this rate decreases to 45% in Spain and 22.5% in Norway (19) (21) (25) (26) (27) .…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard CAM-based triple regimen for 7-14 days is still the first option for eradicating H. pylori in Bangladesh, and LVX-based is the second line treatment [13]. Because antibiotic resistance is increasing worldwide [14,15], it is critical to examine current drug resistance rates in Bangladesh. In this study, we aimed to determine the antibiotic susceptibility of H. pylori to CAM, MNZ, AMX, TCN and LVX in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…In one recent small study from Spain, the reported levofloxacin resistance rate was 14.5%. 5 It is our opinion that bacterial resistance to levofloxacin is the absolute key to treatment success in rescue therapies utilising this antibiotic. We reiterate the low/zero prevalence of resistance of levofloxacin in our local population from our previous survey.…”
mentioning
confidence: 99%